Sebastián Celestino, Carolina López-Ruiz Tartessos and the Phoenicians in Iberia, Oxford University Press, 2016 - Krueger, Michał (Folia Praehistorica Posnaniensia, 2018)
Sebastián Celestino, Carolina López-Ruiz Tartessos and the Phoenicians in Iberia, Oxford University Press, 2016